An Analysis of Figurative Language in the Album Nicole by NIKI - Joana Evelien Alexandra Yap; Rizqi Claudia Wardani (TEKILA: Journal of Language Teaching and Literature, 2025)
This study aims to analyze the types and meanings of figurative language used in NIKI’s album Nicole and to explain how figurative expressions contribute to the interpretation of song lyrics. The research employed a descriptive qualitative design using document analysis as the main method. The data consisted of song lyrics taken from 12 tracks in the album Nicole. Data collection was conducted by listening to the songs repeatedly and examining the official lyrics to ensure accurate interpretation. The analysis was guided by Perrine’s theory to identify and classify types of figurative language, while Leech’s theory of meaning was applied to interpret the semantic meanings conveyed in the lyrics. The findings reveal that the album contains six dominant types of figurative language, namely metaphor, personification, symbol, hyperbole, irony, and allusion. Among these, metaphor was found to be the most frequently used type. The use of figurative language allows the songwriter to express abstract emotions and complex experiences in a more vivid and engaging way. Through figurative expressions, the lyrics portray themes of love, heartbreak, nostalgia, and personal growth, reflecting emotional struggles and life transitions commonly experienced by young adults. Furthermore, the analysis shows that figurative language enhances the emotional depth of the songs by conveying connotative, affective, collocative, thematic, and reflected meanings. These meanings help listeners connect the lyrics with their own personal experiences, making the songs more relatable and meaningful. The findings suggest that figurative language is not merely decorative but plays a crucial role in constructing meaning and emotional impact in song lyrics. This study contributes to the field of linguistics and literary studies by demonstrating how semantic and stylistic analysis can deepen the understanding of meaning in contemporary music. It also provides useful insights for students and researchers interested in figurative language, semantics, and popular song lyrics.